Millennials’ Intention to Invest through Securities Crowdfunding Platform - Nila Febrianti, Ni Made; Darma, Gede Sri (Pandawan, 2023)
This study aims to describe the effect of perceived ease of use, perceived usefulness, perceived risk, social influence, trust, and behavioral intention of using the securities crowdfunding platform. The population of the study is the entire millennial generation who lives in Denpasar City with a total sample of 132 respondents. The data processing technique used is Structural Equation Model (SEM) with AMOS software. The results show that perceived usefulness, social influence, and trust had a direct and significant influence on behavioral intention to use. While the variables perceived ease of use and perceived risk have no direct effect on behavioral intention to use. Perceived ease of use variable has an indirect effect through perceived usefulness and perceived risk has an indirect effect through the trust variable on behavioral intention to use. Trust has the greatest influence on behavioral intention to use the securities crowdfunding platform.